Conference Reflection: On Blindness, the Nature of Elephants, and Educational Research - David Zandvliet (Environmental Association of Southern Africa, 2005)
Adapted from 'The Blind Men and the Elephant' John Godfrey Saxe (1816-1887) Once there were some scholars, to learning much inclined, Who went to see the Elephant (all of them were blind) So each by observation, might satisfy their mind. The first approached the elephant, and, happening to fall, Against a broad and sturdy side, at once began to bawl: 'The elephant, it seems, is nothing but a wall!' Another, feeling a tusk, cried: 'What have we here? (To me it is both reliable and clear) This wonder of an elephant is very like a spear!' A third approached the animal (now wily and awake) Then happening (by grounded chance) to take, Trunk in hand, cried 'the elephant is a snake!' Then a fourth reached for, and felt about the knee (Having paid a substantial entrance fee) Then proudly declared that the elephant was a tree. A fifth, now touching an ear (weathered and tan), States 'what this resembles is clear to the blindest of man, The marvel of the elephant is very much like a fan!' The sixth no sooner had begun about the beast to grope, Then seizing the tail, that fell within his scope, Said finally, 'the elephant is a rope!' And so the scholars, inquired loud and long, Each with opinion exceeding and strong, Though each was in the right, still all were in the wrong! An Invitation to Meet the Elephant The Eastern Cape of South Africa has much to offer. It has popular activities, married with opportunities to interact with people and wildlife of many persuasions. So, when the invitation to participate in the 8th International Invitational Research and Development Seminar on Environmental and Health Education came, it was quite impossible to refuse. Port Elizabeth, said the website: 'beckons with an attractive atmosphere of year-round holiday fun against a backdrop of urban activity ... leisure options encompass a wide range'. Of course, this is only a small and distorted picture of what the Eastern Cape represents to the local inhabitants. So, I had to acknowledge that for now (as some kind of Canadian snowbird) I was going to be coming in 'blind' and I hoped that there would be some reliable guides on hand when I arrived. The tourist website went on to describe parks, botanical gardens, nature reserves and an abundance of wildlife. It notes that in Port Elizabeth, the '1820 Settlers' were introduced to their new land, and there they built some of the graceful homes that still enhance the city's landscape; it is also related that the settlers' trail eventually extended north from here and travelled through Grahamstown (our eventual destination). Of great interest (and also nearby to Port Elizabeth) is the Addo Elephant National Park which is said to support about 350 elephants, in addition to Cape buffalo, black rhino, kudu and over 180 bird species. Keenly, I was anticipating the possibility of a chance meeting with some elephants during this, my second visit to the Eastern Cape.